Fluorine-containing copolymer, fluorine-containing copolymer composition, and crosslinked rubber article

By using specific fluorine-containing copolymers, including tetrafluoroethylene, perfluoro (alkyl vinyl ether), monomers with fluorine atoms and more than 2 polymerizable unsaturated bonds, the hardness and microstructure of the crosslinked rubber articles are improved by using specific fluorine-containing copolymers, including tetrafluoroethylene, perfluoro (alkyl vinyl ether), and monomers with fluorine atoms and more than 2 polymerizable unsatur , solves the problem of poor mold release properties and achieves excellent mold release properties of cross-linked rubber items.

CN119119346APending Publication Date: 2024-12-13AGC INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411162692.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2019-10-30
Filing Date
2020-10-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

There is room for improvement in the mold release properties of the crosslinked rubber articles manufactured in the prior art, especially when the mold is disengaged, resulting in poor mold release properties.

Method used

Using fluorine-containing copolymers based on tetrafluoroethylene, perfluoro (alkyl vinyl ether), monomers with fluorine atoms and two or more polymerizable unsaturated bonds, the cross-linking is improved by adjusting the molar ratio and structure of the monomers. The hardness and microstructure of rubber items can improve mold release.

Benefits of technology

The crosslinked rubber article has been achieved with excellent mold release properties, and the crosslinked rubber is not easy to follow the mold, thereby easily disengaging, improving the efficiency of the manufacturing process and the quality of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005006890490000251
    Figure BDA0005006890490000251
  • Figure BDA0005006890490000252
    Figure BDA0005006890490000252
Patent Text Reader

Abstract

The invention relates to a fluorine-containing copolymer, a fluorine-containing copolymer composition, and a crosslinked rubber article. Provided is a fluorine-containing copolymer with which it is possible to produce a crosslinked rubber article having excellent mold release properties. This fluorine-containing copolymer has a unit based on tetrafluoroethylene, a unit based on perfluoro (alkyl vinyl ether), a unit based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds, and a unit based on a monomer having a nitrile group and a fluorine atom.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of an application filed on October 27, 2020, with application number 202080076473.3, and invention name “Fluorinated copolymer, fluorinated copolymer composition and cross-linked rubber article”. Technical Field

[0002] The present invention relates to a fluorine-containing copolymer, a fluorine-containing copolymer composition and a cross-linked rubber article. Background Art

[0003] Cross-linked rubber products obtained by cross-linking fluorinated copolymers are used in a variety of environments because they are excellent in heat resistance, chemical resistance, oil resistance, weather resistance, etc.

[0004] As a fluorinated copolymer for obtaining such a cross-linked rubber product, Patent Document 1 discloses a fluorinated copolymer having units based on tetrafluoroethylene, units based on perfluoro(alkyl vinyl ether), and units based on a monomer having a nitrile group (cyano group).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 6-263952 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] Crosslinked rubber articles are produced, for example, by supplying a fluorinated copolymer to a mold and heat-molding it. The present inventors produced crosslinked rubber articles using the fluorinated copolymer described in Patent Document 1 and found that there is room for improvement in the releasability of the crosslinked rubber article from the mold.

[0010] The present invention has been made in view of the above-mentioned problems, and an object of the present invention is to provide a fluorinated copolymer and a fluorinated copolymer composition capable of producing a cross-linked rubber article having excellent releasability, and a cross-linked rubber article using the same.

[0011] Solutions for solving problems

[0012] The present inventors have conducted intensive studies on the above-mentioned problems and, as a result, have found that a cross-linked rubber article having excellent mold release properties can be obtained by using a fluorinated copolymer comprising units based on tetrafluoroethylene, units based on perfluoro(alkyl vinyl ether), units based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds, and units based on a monomer having a nitrile group and a fluorine atom, thereby completing the present invention.

[0013] That is, the inventors have found that the above-mentioned problems can be solved by the following configuration.

[0014] [1] A fluorinated copolymer comprising: units based on tetrafluoroethylene, units based on perfluoro(alkyl vinyl ether), units based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds, and units based on a monomer having a nitrile group and a fluorine atom.

[0015] [2] The fluorinated copolymer according to [1], which has a storage modulus G' of 470 kPa or more.

[0016] [3] The fluorinated copolymer according to [1] or [2], wherein the molar ratio of the content of the units based on the monomer having a fluorine atom and two or more polymerizable unsaturated bonds to the content of the units based on the monomer having a nitrile group and a fluorine atom is 0.002 to 20.

[0017] [4] The fluorinated copolymer according to any one of [1] to [3], wherein the perfluoro(alkyl vinyl ether) is a monomer represented by the following formula (1).

[0018] CF2=CF-OR f1 (1)

[0019] In formula (1), R f1 It represents a perfluoroalkyl group having 1 to 10 carbon atoms.

[0020] [5] The fluorinated copolymer according to any one of [1] to [4], wherein the monomer having a fluorine atom and two or more polymerizable unsaturated bonds is a monomer represented by the following formula (2).

[0021] (CR 21 R 22 =CR 23 ) a2 R 24 (2)

[0022] In formula (2), R 21 , R 22 and R 23 each independently represents a hydrogen atom, a fluorine atom, a methyl group or a trifluoromethyl group, a2 represents an integer of 2 to 6, R 24 A perfluorocarbon group having a valence of a2 and having 1 to 10 carbon atoms or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds. 21 , multiple R 22 and multiple R 23 Each are optionally the same as or different from each other.

[0023] [6] The fluorinated copolymer according to [5], wherein the monomer represented by the formula (2) is a monomer represented by the following formula (3) or a monomer represented by the following formula (4).

[0024] (CF2=CF)2R 31 (3)

[0025] In formula (3), R 31 It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

[0026] (CH2=CH)2R 41 (4)

[0027] In formula (4), R 41 It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

[0028] [7] The fluorinated copolymer according to any one of [1] to [6], wherein the monomer having a nitrile group and a fluorine atom is a monomer represented by the following formula (5).

[0029] CR 51 R 52 =CR 53 -R 54 -CN (5)

[0030] In formula (5), R 51 , R 52 and R 53 Each independently represents a hydrogen atom, a fluorine atom or a methyl group, and R 54 It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

[0031] [8] The fluorinated copolymer according to any one of [1] to [7], wherein the content of units based on tetrafluoroethylene is 59 to 80 mol%, the content of units based on perfluoro(alkyl vinyl ether) is 19 to 40 mol%, the content of units based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds is 0.01 to 1.0 mol%, and the content of units based on a monomer having a nitrile group and a fluorine atom is 0.05 to 5 mol%, based on all units of the fluorinated copolymer.

[0032] [9] The fluorinated copolymer according to any one of [1] to [8], wherein the fluorinated copolymer has an iodine atom.

[0033]

[10] A fluorinated copolymer composition comprising the fluorinated copolymer according to any one of [1] to [9] and at least one of a cross-linking agent and a catalyst.

[0034]

[11] The fluorinated copolymer composition according to

[10] , which does not substantially contain a release agent.

[0035]

[12] A cross-linked rubber article obtained by cross-linking the fluorinated copolymer in the fluorinated copolymer composition according to

[10] or

[11] .

[0036] Effects of the Invention

[0037] According to the present invention, there can be provided a fluorinated copolymer and a fluorinated copolymer composition capable of producing a cross-linked rubber article having excellent mold releasability, and a cross-linked rubber article using the same. DETAILED DESCRIPTION

[0038] The meanings of the terms used in the present invention are as follows.

[0039] The numerical range expressed with "to" means a range including the numerical values ​​described before and after "to" as the lower limit and the upper limit.

[0040] "Unit" is a general term for an atomic group derived from one molecule of a monomer directly formed by polymerization of the monomer and an atomic group obtained by chemical conversion of a part of the atomic group. "Unit derived from a monomer" is hereinafter also simply referred to as "unit".

[0041] The "rubber" refers to a rubber exhibiting the properties defined by JIS K 6200 (2008), and is distinguished from a "resin".

[0042] 〔Fluorinated copolymer〕

[0043] The fluorinated copolymer of the present invention comprises units based on tetrafluoroethylene (hereinafter also referred to as “TFE”), units based on perfluoro(alkyl vinyl ether) (hereinafter also referred to as “PAVE”), units based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds (hereinafter also referred to as “DVE”), and units based on a monomer having a nitrile group and a fluorine atom (hereinafter also referred to as “R CN ".) unit.

[0044] The cross-linked rubber article obtained by using the fluorinated copolymer of the present invention has excellent releasability from a mold. The reason for this is not clear in detail, but it is presumed to be due to the following reasons.

[0045] The fluorinated copolymer of the present invention has DVE units and R CN Unit. It is believed that the cross-linked rubber product becomes hard, so when the cross-linked rubber product is removed from the mold, the cross-linked rubber is not easy to follow the mold and is easily removed. In particular, it is speculated that the cross-linked rubber product containing only DVE units or R CNCompared with the fluorinated copolymers of the present invention, the crosslinkable groups of the fluorinated copolymers are uniformly distributed throughout the polymer. Therefore, the mold release property is improved by improving the hardness of the microscopic part of the crosslinked rubber product, which is not different from the physical properties such as general rubber hardness.

[0046] The PAVE unit is a perfluoro(alkyl vinyl ether)-based unit.

[0047] From the viewpoint of excellent polymerization reactivity and rubber properties, PAVE is preferably a monomer represented by the following formula (1).

[0048] CF2=CF-OR f1 (1)

[0049] In formula (1), R f1 represents a perfluoroalkyl group having 1 to 10 carbon atoms. From the viewpoint of better polymerization reactivity, R f1 The carbon number of the moiety is preferably 1-8, more preferably 1-6, further preferably 1-5, and particularly preferably 1-3.

[0050] The perfluoroalkyl group may be linear or branched.

[0051] Specific examples of PAVE include perfluoro(methyl vinyl ether) (hereinafter also referred to as “PMVE”), perfluoro(ethyl vinyl ether) (hereinafter also referred to as “PEVE”), and perfluoro(propyl vinyl ether) (hereinafter also referred to as “PPVE”). Among these, PMVE and PPVE are preferred.

[0052] The DVE unit is a unit based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds.

[0053] Specific examples of the polymerizable unsaturated bond include a carbon atom-carbon atom double bond (C═C) and a carbon atom-carbon atom triple bond (C≡C).

[0054] The number of polymerizable unsaturated bonds in DVE is preferably 2 to 6, more preferably 2 or 3, and particularly preferably 2, from the viewpoint of better polymerization reactivity.

[0055] From the viewpoint of obtaining a more excellent releasable cross-linked rubber product, DVE is preferably a monomer represented by the following formula (2).

[0056] (CR 21 R 22 =CR 23 ) a2 R 24 (2)

[0057] In formula (2), R 21 , R 22and R 23 each independently represents a hydrogen atom, a fluorine atom, a methyl group or a trifluoromethyl group, a2 represents an integer of 2 to 6, R 24 A perfluorocarbon group having a valence of a2 and having 1 to 10 carbon atoms or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds. 21 , multiple R 22 and multiple R 23 Each of them is optionally the same as or different from each other, and is particularly preferably the same as each other.

[0058] a2 is preferably 2 or 3, particularly preferably 2.

[0059] From the viewpoint of better polymerization reactivity of DVE, R 21 , R 22 , R 23 is a fluorine atom or a hydrogen atom, more preferably R 21 , R 22 , R 23 All of them are fluorine atoms or all of them are hydrogen atoms. From the viewpoint of better releasability of the cross-linked rubber article, R 21 , R 22 , R 23 All of them are fluorine atoms.

[0060] R 24 It may be linear, branched or cyclic, preferably linear or branched, and particularly preferably linear. 24 The carbon number of the moiety is preferably 2-8, more preferably 3-7, further preferably 3-6, and particularly preferably 3-5.

[0061] R 24 The rubber compound may or may not have an etheric oxygen atom, but preferably has an etheric oxygen atom from the viewpoint of better crosslinking reactivity and rubber properties.

[0062] R 24 The number of etheric oxygen atoms in R is preferably 1 to 6, more preferably 1 to 3, and particularly preferably 1 or 2. 24 The etheric oxygen atom in R 24 The end of.

[0063] Specific examples of suitable monomers among the monomers represented by formula (2) include monomers represented by the following formula (3) and monomers represented by the following formula (4).

[0064] (CF2=CF)2R 31 (3)

[0065] In formula (3), R 31It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

[0066] (CH2=CH)2R 41 (4)

[0067] In formula (4), R 41 It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

[0068] Specific examples of the monomer represented by formula (3) include CF2=CFO(CF2)2OCF=CF2, CF2=CFO(CF2)3OCF=CF2, CF2=CFO(CF2)4OCF=CF2, CF2=CFO(CF2)6OCF=CF2, CF2=CFO(CF2)8OCF=CF2, CF2=CFO(CF2)2OCF(CF3)CF2OCF=CF2, CF2=CFO(CF 2)2O(CF(CF3)CF2O)2CF=CF2, CF2=CFOCF2O(CF2CF2O)2CF=CF2, CF2=CFO(CF2O)3O(CF(CF3)CF2O)2C F=CF2, CF2=CFOCF2CF(CF3)O(CF2)2OCF(CF3)CF2OCF=CF2, CF2=CFOCF2CF2O(CF2O)2CF2CF2OCF=CF2.

[0069] Among the monomers represented by formula (3), specific examples of more suitable monomers include CF2=CFO(CF2)3OCF=CF2 (hereinafter also referred to as "C3DVE") and CF2=CFO(CF2)4OCF=CF2 (hereinafter also referred to as "C4DVE" or "PBDVE").

[0070] Specific examples of the monomer represented by formula (4) include CH2=CH(CF2)2CH=CH2, CH2=CH(CF2)4CH=CH2, and CH2=CH(CF2)6CH=CH2.

[0071] Among the monomers represented by formula (4), a specific example of a more suitable monomer is CH2=CH(CF2)6CH=CH2 (hereinafter also referred to as "C6DV").

[0072] When DVE is copolymerized, a part of the polymerizable double bonds at the terminals of DVE react during polymerization to obtain a fluorinated copolymer having branches.

[0073] R CNThe unit is a unit based on a monomer having a nitrile group and a fluorine atom. The fluorinated copolymer has R CN Unit, whereby the cross-linked rubber article is excellent in heat resistance.

[0074] From the perspective of polymerization reactivity, R CN It is preferred to have a polymerizable unsaturated bond, and it is particularly preferred to have one polymerizable unsaturated bond. Specific examples of the polymerizable unsaturated bond are as described above.

[0075] From the perspective of better mold release and heat resistance of cross-linked rubber products, R CN Preferred is a monomer represented by the following formula (5).

[0076] CR 51 R 52 =CR 53 -R 54 -CN (5)

[0077] In formula (5), R 51 , R 52 and R 53 Each independently represents a hydrogen atom, a fluorine atom or a methyl group, and R 54 It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

[0078] From R CN From the viewpoint of excellent polymerization reactivity, R 51 , R 52 , R 53 is a fluorine atom or a hydrogen atom, more preferably R 51 , R 52 , R 53 All of them are fluorine atoms or all of them are hydrogen atoms. From the viewpoint of better mold release and heat resistance of the cross-linked rubber product, R 51 , R 52 , R 53 All of them are fluorine atoms.

[0079] R 54 It may be linear, branched or cyclic, and is preferably linear or branched. 54 The carbon number of the moiety is preferably 2-8, more preferably 3-7, further preferably 3-6, and particularly preferably 3-5.

[0080] R 54 The rubber may or may not have an etheric oxygen atom, but preferably has an etheric oxygen atom from the viewpoint of better rubber properties.

[0081] R 54 The number of etheric oxygen atoms in the ether is preferably 1 to 3, and particularly preferably 1 or 2.

[0082] Specific examples of the monomer represented by formula (5) include CF2=CFOCF2CF(CF3)OCF2CF2CN (hereinafter also referred to as "8CNVE"), CF2=CFO(CF2)5CN (hereinafter also referred to as "MV5CN"), CF2=CFOCF2CF2CF2OCF(CF3)CN, and CF2=CFO(CF2)3CN. From the perspective of better demolding properties and heat resistance of cross-linked rubber products, 8CNVE and MV5CN are preferred.

[0083] The fluorinated copolymer may have a composition based on TFE, PAVE, DVE and R CN Hereinafter, units based on monomers other than TFE, PAVE, DVE and R CN The units of monomers other than are collectively referred to as "other monomers".

[0084] Specific examples of other monomers include units based on a monomer represented by the following formula (6) (hereinafter also referred to as “units of formula (6)”), vinylidene fluoride (hereinafter also referred to as “VdF”) units, hexafluoropropylene (hereinafter also referred to as “HFP”) units, chlorotrifluoroethylene (hereinafter also referred to as “CTFE”) units, ethylene units, and monomers other than TFE, PAVE, DVE, and R CN , the monomer represented by formula (6), VdF, HFP and a monomer having a halogen atom other than CTFE (hereinafter also referred to as other monomers having a halogen atom) (for example, bromotrifluoroethylene, iodotrifluoroethylene).

[0085] Formula (6) is as follows.

[0086] CF2=CF-OR f2 (6)

[0087] In formula (6), R f2 R represents a perfluoroalkyl group having 1 to 8 carbon atoms and containing 1 to 5 etheric oxygen atoms. f2 The carbon number of alkylene oxide is preferably 1-6, particularly preferably 1-5.

[0088] Specific examples of the monomer represented by formula (6) include perfluoro(3,6-dioxa-1-heptene), perfluoro(3,6-dioxa-1-octene), and perfluoro(5-methyl-3,6-dioxa-1-nonene).

[0089] From the viewpoint of further improving the heat resistance of the cross-linked rubber product, the content of the TFE unit is preferably from 59 to 80 mol %, more preferably from 63 to 75 mol %, particularly preferably from 66 to 72 mol % based on the total units of the fluorinated copolymer.

[0090] From the viewpoint of more excellent elasticity of the cross-linked rubber product, the content of the PAVE unit is preferably from 19 to 40 mol %, more preferably from 24 to 36 mol %, particularly preferably from 27 to 33 mol % based on the total units of the fluorinated copolymer.

[0091] From the viewpoint of obtaining more excellent releasability of the cross-linked rubber article, the content of the DVE unit is preferably from 0.01 to 1.0 mol %, more preferably from 0.03 to 0.6 mol %, particularly preferably from 0.05 to 0.4 mol %, based on the total units of the fluorinated copolymer.

[0092] From the perspective of better mold release and heat resistance of cross-linked rubber products, R CN The content of the unit is preferably from 0.05 to 5 mol %, more preferably from 0.1 to 3 mol %, particularly preferably from 0.2 to 1.5 mol %, based on all the units of the fluorinated copolymer.

[0093] When the fluorinated copolymer contains other monomer units, the content of the other monomer units is preferably 0.01 to 20 mol %, more preferably 0.5 to 10 mol %, particularly preferably 1 to 5 mol % based on all units of the fluorinated copolymer from the viewpoint of heat resistance of the cross-linked rubber product.

[0094] From the viewpoint of better mold release and heat resistance of the cross-linked rubber product, it is preferred that the content of TFE units is 59 to 80 mol%, the content of PAVE units is 19 to 40 mol%, the content of DVE units is 0.01 to 1.0 mol%, and the content of R is 1.0 to 2.0 mol% based on the total units of the fluorinated copolymer. CN The content of the unit is 0.05 to 5 mol%.

[0095] The content of DVE units relative to R CN The molar ratio of the content of the unit (DVE unit / R CN The molar ratio is preferably 0.002 to 20, more preferably 0.03 to 2, further preferably 0.1 to 1, and particularly preferably 0.35 to 0.59. When the molar ratio is within the above range, both the mold release property and the heat resistance of the cross-linked rubber article can be achieved at a high level.

[0096] It should be noted that the DVE unit relative to all units in the fluorinated copolymer is calculated based on the amount of DVE used in the manufacture of the fluorinated copolymer (the amount of DVE used). Here, the "amount of DVE used" is a value obtained by subtracting the amount of unpolymerized DVE from the amount of DVE added to the polymerization container (the amount of DVE input). It is believed that the unpolymerized DVE is contained in the filtrate after aggregating the latex after polymerization and taking out the fluorinated copolymer and the filtrate remaining after washing the latex, and the amount can be measured by measuring fluoride ions using, for example, an ion chromatograph measuring device.

[0097] In addition, the ratio of TFE units, PAVE units and R to all units in the fluorinated copolymer is CN Unit Pass 19 F-nuclear magnetic resonance (NMR) analysis. 19 F-NMR analysis to determine the TFE unit in the fluorinated polymer: PAVE unit: R CN Then, the value obtained by subtracting the content of DVE units (mol %) from 100 mol % was substituted into the value obtained by 19 TFE unit in the fluorinated polymer determined by F-nuclear magnetic resonance (NMR) analysis: PAVE unit: R CN Unit (molar ratio), calculate the content of each unit.

[0098] The fluorinated copolymer may have an iodine atom. In this case, it is preferred that the fluorinated copolymer (polymer chain) has an iodine atom at the terminal.

[0099] Examples of the iodine atom include an iodine atom derived from an iodine compound functioning as a chain transfer agent described later and an iodine atom in a unit based on a monomer having an iodine atom among other monomers having a halogen atom such as iodotrifluoroethylene described above. An iodine atom derived from an iodine compound functioning as a chain transfer agent is preferred.

[0100] When the fluorinated copolymer has iodine atoms, the content thereof is preferably 0.01 to 5.0 mass %, more preferably 0.05 to 2.0 mass %, particularly preferably 0.05 to 1.0 mass % relative to the total mass of the fluorinated copolymer. When the content of iodine atoms is within the above range, the crosslinking reactivity with the fluorinated copolymer is improved, thereby providing excellent mechanical properties of the crosslinked rubber article.

[0101] <Physical properties>

[0102] The storage modulus G' of the fluorinated copolymer is preferably 450 kPa or more, particularly preferably 470 kPa or more. The reason for this is not clear, but if the storage modulus G' is 470 kPa or more, the compression set of the cross-linked rubber product at high temperature can be further reduced.

[0103] The storage elastic modulus G′ of the fluorinated copolymer is preferably 650 kPa or less, more preferably 630 kPa or less, particularly preferably 600 kPa or less, from the viewpoint of excellent processability.

[0104] As an example of a method for obtaining a fluorinated copolymer having a storage elastic modulus G' of at least 470 kPa, there is mentioned a method of adjusting the order of addition, the number of additions, etc. of each monomer at the time of production of the fluorinated copolymer.

[0105] Here, the storage modulus G' is a standard for the average molecular weight. A higher storage modulus G' indicates a larger molecular weight, and a lower storage modulus G' indicates a smaller molecular weight.

[0106] The storage modulus G' of the fluorinated copolymer in the present invention is a value measured in accordance with ASTM D6204, and the detailed measurement conditions are shown in the Examples.

[0107] The storage modulus G'1 and storage modulus G' of the fluorinated copolymer of the present invention are 0.1 These are values ​​measured in accordance with ASTM D 4440, and the detailed measurement conditions are shown in the Examples.

[0108] <Method for producing fluorinated copolymer>

[0109] As an example of the method for producing the fluorinated copolymer of the present invention, there is mentioned a method of copolymerizing the above-mentioned monomers in the presence of a radical polymerization initiator.

[0110] As the radical polymerization initiator, a water-soluble polymerization initiator or a redox polymerization initiator is preferred.

[0111] Specific examples of the water-soluble polymerization initiator include persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate, and organic polymerization initiators such as disuccinic acid peroxide and azobisisobutylamidine dihydrochloride. Among these, persulfates are preferred, and ammonium persulfate is more preferred.

[0112] As the redox polymerization initiator, there can be mentioned a polymerization initiator in which a persulfate and a reducing agent are combined. Among them, a polymerization initiator that can polymerize each monomer at a polymerization temperature in the range of 0 to 60° C. is preferred. As specific examples of persulfates constituting the redox polymerization initiator, there can be mentioned alkali metal salts of persulfates such as ammonium persulfate, sodium persulfate, and potassium persulfate, preferably ammonium persulfate. As specific examples of reducing agents combined with persulfates, there can be mentioned thiosulfates, sulfites, hydrogensulfites, pyrosulfites, and hydroxymethanesulfinates, preferably hydroxymethanesulfinates, and particularly preferably sodium hydroxymethanesulfinate.

[0113] In the process for producing the fluorinated copolymer of the present invention, the above-mentioned monomers may be copolymerized in the presence of a radical polymerization initiator and a chain transfer agent.

[0114] The chain transfer agent is preferably an iodine compound, and particularly preferably an iodine compound represented by formula RI2. In the above formula, R represents an alkylene group having 3 or more carbon atoms (preferably 3 to 8 carbon atoms) or a perfluoroalkylene group.

[0115] Specific examples of the iodine compound represented by formula RI2 include 1,3-diiodopropane, 1,4-diiodobutane, 1,6-diiodohexane, 1,8-diiodooctane, 1,3-diiodoperfluoropropane, 1,4-diiodoperfluorobutane, 1,6-diiodoperfluorohexane, and 1,8-diiodoperfluorooctane.

[0116] As the iodine compound, an iodine compound having a perfluoroalkylene group is preferred, and 1,4-diiodoperfluorobutane is particularly preferred.

[0117] When the above-mentioned monomers are copolymerized in the presence of these iodine compounds, iodine atoms can be introduced into the fluorinated copolymer.

[0118] Regarding the components other than those mentioned above used in the production of the fluorinated copolymer and details of the production method, reference can be made to the method described in paragraphs 0019 to 0034 of International Publication No. 2010 / 082633.

[0119] [Fluorinated copolymer composition]

[0120] The fluorinated copolymer composition of the present invention comprises the above-mentioned fluorinated copolymer and at least one of a crosslinking agent and a catalyst. The fluorinated copolymer composition may comprise only one of the crosslinking agent and the catalyst, or may comprise both of them.

[0121] Specific examples of the crosslinking agent include organic peroxides, polyols, amines, and triazines. Organic peroxides are preferred because the crosslinked rubber product has excellent productivity, heat resistance, and chemical resistance.

[0122] Specific examples of the organic peroxide include dialkyl peroxides, α,α′-bis(tert-butylperoxy)-p-diisopropylbenzene, α,α′-bis(tert-butylperoxy)-m-diisopropylbenzene, benzoyl peroxide, tert-butylbenzene peroxide, and 2,5-dimethyl-2,5-di(benzoylperoxy)hexane.

[0123] Specific examples of dialkyl peroxides include 1,1-di(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroxyperoxide, tert-butylcumene peroxide, dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, tert-butyl peroxymaleate, and tert-butyl peroxyisopropyl carbonate.

[0124] Examples of the amine include compounds having two or more amino groups (hereinafter also referred to as “polyamine compounds”).

[0125] The polyamine compound may be a compound in which hydrogen atoms of an aliphatic hydrocarbon are substituted with amino groups, or a compound in which hydrogen atoms of an aromatic hydrocarbon are substituted with amino groups. From the viewpoint of achieving more excellent effects of the present invention, a compound in which hydrogen atoms of an aromatic hydrocarbon are substituted with amino groups is preferred.

[0126] The polyamine compound preferably contains fluorine atoms, because the compatibility with the specific fluorine-containing copolymer becomes good, and thus a cross-linked rubber product having a smaller compression set at high temperature can be obtained.

[0127] Specific examples of the polyamine compound include hexamethylenediamine, hexamethylenediamine carbamate, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis(3-amino-4-hydroxyphenyl)propane, 2,2-bis(3-amino-4-hydroxyphenyl)hexafluoropropane (hereinafter also referred to as "BOAP". Another name: bisaminophenol AF), 2,2-bis(3,4-diaminophenyl)propane, 2,2-bis(3,4-diaminophenyl)hexafluoropropane, 2,2-bis(3-amino-4-(N-phenylamino)phenyl)hexafluoropropane, 4,4'-methylenedianiline, metaphenylenediamine, adipic acid dihydrazide, and the compound represented by formula (XII) of Japanese Patent No. 5833657. Among them, BOAP is preferred from the viewpoint of having a better compression set.

[0128] When the fluorinated copolymer composition contains a crosslinking agent, the content of the crosslinking agent is preferably 0.3 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, and particularly preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the fluorinated copolymer. When the content of the crosslinking agent is within the above range, the balance between strength and elongation of the crosslinked rubber article is excellent.

[0129] Specific examples of the catalyst include organic tin compounds, and organic tin compounds are preferred because the productivity, heat resistance, and chemical resistance of the cross-linked rubber product are excellent.

[0130] Specific examples of the organic tin compound include tetramethyltin, tetra(n-butyl)tin, and tetraphenyltin.

[0131] When the fluorinated copolymer composition contains a catalyst, the content of the catalyst is preferably 0.3 to 10 parts by mass, more preferably 0.3 to 5 parts by mass, particularly preferably 0.5 to 3 parts by mass, relative to 100 parts by mass of the fluorinated copolymer. When the content of the catalyst is within the above range, the balance between strength and elongation of the cross-linked rubber article is excellent.

[0132] <Other ingredients>

[0133] The fluorinated copolymer composition may contain other ingredients other than those mentioned above within the range that does not impair the effect of the present invention. As other ingredients, crosslinking aids (e.g., triallyl cyanurate, triallyl isocyanurate, trimethylallyl isocyanurate), acid absorbents (e.g., fatty acid esters, fatty acid metal salts, oxides of divalent metals (magnesium oxide, calcium oxide, zinc oxide, lead oxide, etc.)), fillers and reinforcing materials (e.g., carbon black, barium sulfate, calcium metasilicate, calcium carbonate, titanium oxide, silicon dioxide, clay, talc), coking retarders (e.g., phenolic hydroxyl-containing compounds such as bisphenol A, quinones such as hydroquinone, α-methylstyrene dimers such as 2,4-di(3-isopropylphenyl)-4-methyl-1-pentene), crown ethers (e.g., 18-crown-6), and mold release agents (e.g., sodium stearate).

[0134] The fluorinated copolymer composition may contain a release agent, but the release agent may seep out from the surface of the cross-linked rubber article obtained using the fluorinated copolymer composition, causing contamination. Therefore, from the perspective of being suitable for use as a component (e.g., O-ring) possessed by a semiconductor manufacturing device, the fluorinated copolymer composition preferably contains substantially no release agent.

[0135] Here, “the fluorinated copolymer composition contains substantially no releasing agent” means that the content of the releasing agent is at most 0.1 part by mass, preferably at most 0.01 part by mass, particularly preferably 0 part by mass, based on 100 parts by mass of the fluorinated copolymer.

[0136] When the fluorinated copolymer composition contains other components, the total content of other components is preferably more than 0 part by mass and at most 30 parts by mass, more preferably 1 to 25 parts by mass, particularly preferably 5 to 15 parts by mass, based on 100 parts by mass of the fluorinated copolymer.

[0137] The fluorinated copolymer composition may be prepared by mixing the above-mentioned components. The mixing of the components can be carried out using a rubber mixing device such as a roll, a kneader, a Banbury mixer or an extruder.

[0138] In addition, the mixture can be formed after obtaining the mixture mixed with the above-mentioned components. As a specific example of the molding method of the mixture, compression molding, injection molding, extrusion molding, calendering molding, or a method for molding by dissolving in a solvent and impregnating or applying to a substrate etc. can be enumerated.

[0139] <Physical properties>

[0140] As an index of the crosslinking property of the fluorinated copolymer composition, M measured by the method of the Examples described later can be cited. H -M L (Hereinafter, this is also referred to as "crosslinking degree.") The larger the numerical value of the crosslinking degree is, the more crosslinked structures the crosslinked rubber has.

[0141] The degree of crosslinking of the crosslinked rubber is preferably 80 dNm or less, more preferably 60 dNm or less, and particularly preferably 40 dNm or less. When the degree of crosslinking of the crosslinked rubber is within the above range, the crosslinked rubber has excellent flexibility.

[0142] The degree of crosslinking of the crosslinked rubber is preferably 3 dNm or more, more preferably 5 dNm or more, and particularly preferably 10 dNm or more. When the degree of crosslinking of the crosslinked rubber is within the above range, the compression set of the crosslinked rubber is excellent.

[0143] 〔Cross-linked rubber products〕

[0144] The cross-linked rubber article of the present invention is a rubber article obtained by cross-linking the fluorinated copolymer in the above-mentioned fluorinated copolymer composition.

[0145] As a method for crosslinking the fluorinated copolymer in the fluorinated copolymer composition, a method of crosslinking by heating the fluorinated copolymer composition is preferred.

[0146] Specific examples of the crosslinking method by heating include heat press crosslinking, steam crosslinking and hot air crosslinking. These methods may be appropriately selected in consideration of the shape and application of the fluorinated copolymer or the fluorinated copolymer composition.

[0147] The heating conditions are preferably 100 to 400° C. for 1 second to 24 hours.

[0148] The crosslinked rubber obtained by heating the fluorinated copolymer composition (primary crosslinking) may be further heated to perform secondary crosslinking. The mechanical properties, compression set and other properties of the crosslinked rubber can be stabilized or improved by performing secondary crosslinking.

[0149] The heating conditions for the secondary crosslinking are preferably 80 to 350° C. for 30 minutes to 48 hours.

[0150] As a crosslinking method other than crosslinking the fluorinated copolymer by heating, there is mentioned a method of crosslinking the fluorinated copolymer composition by irradiating radiation. Specific examples of the radiation to be irradiated include electron beams and ultraviolet rays.

[0151] <Physical properties>

[0152] The tensile strength (tensile breaking strength) of the cross-linked rubber product is preferably 1 to 50 MPa, particularly preferably 10 to 35 MPa, from the viewpoint of excellent rubber properties.

[0153] From the viewpoint of excellent rubber properties, the 100% modulus (tensile stress at 100% elongation) of the cross-linked rubber product is preferably 0.2 to 15 MPa, particularly preferably 0.5 to 9 MPa.

[0154] From the viewpoint of excellent rubber properties, the tensile elongation (elongation at break) of the cross-linked rubber product is preferably 100 to 1000%, particularly preferably 120 to 600%.

[0155] The tensile strength, 100% modulus and elongation at break of the cross-linked rubber product are values ​​measured according to the method of JIS K 6251: 2010 (corresponding to the international standard ISO 37: 2005).

[0156] The hardness (Shore-A) of the cross-linked rubber product is preferably 65 to 100, more preferably 68 to 90, and particularly preferably 70 to 85, from the viewpoint of excellent rubber properties.

[0157] The hardness (Shore-A) of the cross-linked rubber product is a value measured using a plate-shaped molded product (thickness 1 mm) of the cross-linked rubber product in accordance with JIS K 6253-1:2012 using a type A durometer.

[0158] The compression set at 250°C of the cross-linked rubber article is preferably 65% ​​or less, more preferably 60% or less, further preferably 50% or less, particularly preferably 40% or less, from the viewpoint that the fluorinated copolymer is well cross-linked and the cross-linked rubber article has excellent shape recovery after pressurization.

[0159] The lower limit of the compression set at 250° C. of the cross-linked rubber article is preferably 0%, and most preferably the compression set at 250° C. of the cross-linked rubber article is 0%.

[0160] The compression set at 250° C. of the cross-linked rubber product is a value measured in accordance with JIS K 6262 using a plate-shaped molded product (thickness 1 mm) of the cross-linked rubber product.

[0161] The above-mentioned physical properties of the cross-linked rubber article can be adjusted by, for example, the production conditions of the above-mentioned fluorinated copolymer (e.g., the order of addition of each monomer, the number of additions, and the amount of addition), the types and contents of each component contained in the above-mentioned fluorinated copolymer composition, and the production conditions of the cross-linked rubber article (e.g., cross-linking conditions).

[0162] <Purpose>

[0163] The crosslinked rubber article is suitable for materials such as O-rings, sheets, gaskets, oil seals, diaphragms, V-rings, etc. In addition, it can also be applied to heat-resistant and chemical-resistant sealing materials, heat-resistant and oil-resistant sealing materials, wire covering materials, sealing materials for semiconductor devices, corrosion-resistant rubber coatings, sealing materials for urea-based greases, etc., rubber coatings, adhesive rubbers, hoses (horse), tubes (tube), calendered sheets (rolls), sponges, rubber rollers, components for oil extraction, heat sinks, solution crosslinked bodies, rubber sponges, bearing seals (for urea greases, etc.), linings (chemical-resistant), insulating sheets for automobiles, insulating sheets for electronic devices, rubber bands for watches, fillers for endoscopes (amine-resistant), bellows (processed from calendered sheets), water heater fillers / valves, fender materials (marine civil engineering, ships), fibers / non-woven fabrics (protective clothing, etc.), base sealing materials, rubber handbags, stators of single-axis eccentric screw pumps, components for urea SCR systems, anti-vibration agents, shock absorbers, sealants, additives in their materials, and uses for toys.

[0164] Examples

[0165] Hereinafter, the present invention will be described in detail with examples. Examples 1 to 6 are examples, and Examples 7 and 8 are comparative examples. However, the present invention is not limited to these examples. It should be noted that the content of each component in the tables described later represents a mass basis unless otherwise specified.

[0166] 〔Content of units based on each monomer in the fluorine-containing copolymer〕

[0167] The content (mol%) of DVE units relative to all units of the fluorine-containing copolymer is calculated based on the amount of DVE used in the production of the fluorine-containing copolymer (the amount of DVE used).

[0168] In addition, the content (mol%) of TFE units, PAVE units, and R CN units relative to all units of the fluorine-containing copolymer is based on 19 19F - nuclear magnetic resonance (NMR) analysis for calculation.

[0169] <Calculation of the content of DVE units relative to all units of the fluorine-containing copolymer>

[0170] The filtrate after aggregating the polymerized latex and taking out the fluorine-containing copolymer and the filtrate remaining after washing the latex were filtered with a disc filter, and the resulting liquid was analyzed using an ion chromatography measuring device (manufactured by Daia Instruments, a device combined with a pretreatment device for ion chromatography AQF - 100 type for automatic sample combustion and an ion chromatograph).

[0171] When fluoride ions are detected at 3 mass % or more relative to the input amount of DVE, the amount of DVE used is the value obtained by subtracting the amount of DVE in the liquid calculated based on the measurement results of the above ion chromatography from the amount of DVE added to the reactor (the input amount of DVE).

[0172] On the other hand, when 3 mass % or more of fluoride ions relative to the charged amount of DVE was not detected, it was considered that all the DVE used in the feed was polymerized, and the amount of DVE used was the charged amount of DVE.

[0173] Based on the thus obtained amount of the DVE unit used, the content (mol %) of the DVE unit based on all the units of the fluorinated copolymer was calculated.

[0174] [Storage modulus G' of fluorinated copolymer]

[0175] The storage modulus G' of the fluorinated copolymer was measured using a rubber processing analyzer (RPA2000 manufactured by Alpha Technologies) in accordance with ASTM D6204 at a temperature of 100°C, an amplitude of 0.5 degrees, and a vibration frequency of 50 times / min. The storage modulus G' of the fluorinated copolymer is used as an index of the fluidity of the cross-linked rubber article during molding.

[0176] 〔Storage modulus G' of fluorinated copolymer 0.1 , G'1〕

[0177] The storage modulus G' of the fluorinated copolymer was determined using a rubber processing analyzer (RPA2000 manufactured by Alpha Technologies) in accordance with ASTM D4440 at a temperature of 140°C and a shear rate of 0.1 degree / second and 1 degree / second. 0.1 , and G'1.

[0178] [Degree of crosslinking of fluorinated copolymer composition]

[0179] The crosslinking characteristics of the fluorinated copolymer composition were measured using a crosslinking characteristics tester (manufactured by Alpha Technologies, trade name "RPA2000") in accordance with ASTM D5289 under the conditions of 177°C, 12 minutes and an amplitude of 3 degrees.

[0180] Determination of M H Indicates the maximum torque, M L Indicates the minimum value of torque, M H -M L (By M H Subtract M LThe value obtained after the crosslinking is expressed as the degree of crosslinking (unit: dNm). The crosslinking property is an index of the crosslinking reactivity of the fluorinated copolymer, M H -M L The larger the value of , the better the cross-linking reactivity.

[0181] 〔Specific gravity of fluorinated copolymers and cross-linked rubber products〕

[0182] The specific gravity of the fluorinated copolymer and the cross-linked rubber article was measured using a densitometer (manufactured by Shinko Electronics Co., Ltd.) in accordance with JIS K6220-1:2015.

[0183] [Tensile strength, 100% modulus, and tensile elongation of cross-linked rubber products]

[0184] Using a test piece punched out from a plate-like cross-linked rubber article (thickness 1 mm) with a No. 4 dumbbell, the tensile strength, 100% modulus and tensile elongation were measured in accordance with JIS K6251:2010 (corresponding to international standard ISO 37:2005).

[0185] In addition, as a measuring device, a tensile testing machine with data processing (Quick Reader TS-2530, manufactured by Ueshima Manufacturing Co., Ltd.) was used.

[0186] In addition, each test was performed using three test pieces, and the arithmetic average of the measured values ​​of the three test pieces was recorded.

[0187] 〔hardness〕

[0188] Using a test piece of a cross-linked rubber product, the hardness (Shore-A) was measured using a type A durometer in accordance with JIS K 6253-3:2012.

[0189] In addition, as a measuring device, an automatic hardness tester for rubber (Digi test shore A, manufactured by H.H. Burleys Co.) was used.

[0190] The test was performed using three test pieces, and the arithmetic average of the measured values ​​of the three test pieces was recorded.

[0191] 〔Compression set〕

[0192] The compression set (%) of the crosslinked rubber product was measured when the test piece was kept at 250°C for 70 hours in accordance with JIS K 6262. The smaller the compression set value, the better the recovery of the crosslinked rubber product, that is, the crosslinking was well performed.

[0193] The test was performed using three test pieces, and the arithmetic average of the measured values ​​of the three test pieces was recorded.

[0194] 〔Heat aging test〕

[0195] After measuring the thickness of the test piece of the cross-linked rubber product with a thickness gauge, the test piece was heated at 300° C. for 70 hours in an air atmosphere (heat aging).

[0196] After the heat-aged test piece was cooled to room temperature, the tensile strength, 100% modulus, and tensile elongation after heat aging were measured using the cooled test piece under the same conditions as the above-mentioned test method.

[0197] The test was performed using three test pieces, and the arithmetic average of the measured values ​​of the three test pieces was recorded.

[0198] Based on the measured value of the test piece before heat aging (normal test value) and the measured value of the test piece after heat aging (test value after heat aging), the change rate before and after the heat aging test (heat aging test change rate) is calculated by the following formula. The closer the change rate is to 0%, the better the heat resistance is.

[0199] Heat aging test change rate (%) = 100 × {(normal test value) - (test value after heat aging)} / (normal test value)

[0200] [Mold release test]

[0201] The fluorinated copolymer composition was introduced into a sheet-shaped mold, and the fluorinated copolymer composition was cross-linked at 180°C for 20 minutes to obtain a cross-linked rubber article (100 mm in length × 60 mm in width × 1 mm in thickness) in a state of being attached to the mold. Immediately after the cross-linking reaction was completed, an air gun (product name: CYCLONE DUSTER, manufactured by Chuo Air Machinery Co., Ltd.) was used to spray air to the interface between the cross-linked rubber article and the mold, and the demolding property was evaluated according to the following evaluation criteria.

[0202] Note that since the air was sprayed immediately after the cross-linking reaction was completed, it is considered that the temperature of the cross-linked article during the air spraying was close to 180°C.

[0203] <Air injection conditions using an air gun>

[0204] Pressure: 0.5MPa

[0205] Air injection time: 3 seconds

[0206] <Evaluation Criteria>

[0207] ○: The cross-linked rubber article was released from the mold.

[0208] ×: The cross-linked rubber article did not come off the mold.

[0209] [Example 1]

[0210] <Production of Fluorinated Copolymer 1>

[0211] After degassing a stainless steel pressure-resistant reactor with an internal volume of 20 L equipped with anchor blades, 7.2 L of ultrapure water, 880 g of a 30% solution of C2F5OCF2CF2OCF2COONH4 as an emulsifier, 7.3 g of 8CNVE, 17.7 g of C3DVE, and 15.9 g of a 5% aqueous solution of disodium hydrogen phosphate dodecahydrate were added to replace the gas phase with nitrogen. While stirring at a speed of 375 rpm using an anchor blade, 137 g of TFE and 635 g of PMVE were pressed into the container, and the internal temperature was raised to 80°C. The internal pressure of the reactor was 0.90 MPa [gauge]. 40 mL of a 3% aqueous solution of ammonium persulfate (APS) was added to start polymerization. When the addition ratio of the monomers injected before the start of polymerization (hereinafter also referred to as "initial addition monomers") is expressed as a molar ratio, it is TFE:PMVE:8CNVE:C3DVE=26.0:72.6:0.4:1.0.

[0212] After the start of polymerization, the monomers are introduced as follows as the polymerization proceeds. Hereinafter, the operation of introducing the monomers after the start of polymerization is also referred to as "post-addition", and the monomer introduced after the start of polymerization is also referred to as "post-added monomer".

[0213] When the pressure inside the reactor dropped to 0.89 MPa [gauge], TFE was introduced to raise the pressure inside the reactor to 0.90 MPa [gauge]. This operation was repeated, and every time 119.3 g of TFE was introduced, 3.6 g of 8CNVE, 74 g of PMVE, and 3.6 g of 8CNVE were introduced in sequence.

[0214] When the polymerization rate slowed down, a 3% by mass aqueous solution of APS was added appropriately. The total amount of the 3% by mass aqueous solution of APS added after the start of the polymerization was 51 mL.

[0215] At the end of the cycle when the total added mass of TFE became 1073.7 g, 119.3 g of TFE was pressed in. When the total added mass of the post-added TFE became 1193 g, the addition of the post-added monomers was stopped, and the temperature in the reactor was cooled to 10°C to stop the polymerization reaction and obtain a latex containing a fluorinated copolymer. The polymerization time was 375 minutes. In addition, the total added mass of each post-added monomer was: 1193 g for TFE, 666 g for PMVE, and 64.8 g for 8CNVE, which was converted into a molar ratio of: TFE: PMVE: 8CNVE = 74.1: 24.9: 1.0.

[0216] The latex was added to a 5 mass % aqueous solution of potassium aluminum sulfate to aggregate and separate the fluorinated copolymer. The fluorinated copolymer was filtered, washed with ultrapure water, and vacuum dried at 50° C. to obtain a white fluorinated copolymer 1. The content (molar ratio) of each unit in the obtained fluorinated copolymer 1 was: TFE unit / PMVE unit / 8CNVE unit / C3DVE unit=68.9 / 30.3 / 0.5 / 0.3.

[0217] It should be noted that the filtrate after aggregating the latex after polymerization and taking out the fluorinated copolymer and the filtrate remaining after washing the latex were filtered with a disk filter, and the obtained liquid was analyzed with an ion chromatograph. As a result, no fluoride ions were detected in an amount of 3% by mass or more relative to the input amount of C3DVE. Therefore, it was considered that all the C3DVE used in the feed was polymerized, and the content of C3DVE units relative to all units in the polymer was calculated based on the input amount of C3DVE.

[0218] <Production of Fluorinated Copolymer Composition 1>

[0219] The components were mixed in a ratio of 100 parts by mass of the fluorinated copolymer 1, 8 parts by mass of carbon black (SEAST 9 manufactured by TOKAI CARBON CO., LTD.), 3 parts by mass of tetraphenyltin (manufactured by Tokyo Chemical Industry Co., Ltd.), and 0.1 parts by mass of 18-crown-6 (manufactured by FUJIFILM Wako Pure Chemical Corporation), and kneaded on a two-roll mill to obtain a fluorinated copolymer composition 1.

[0220] <Manufacturing of Cross-linked Rubber Article 1>

[0221] The fluorinated copolymer composition 1 was crosslinked and molded at 180°C for 20 minutes to obtain a crosslinked rubber sheet (primary crosslinking) of 100 mm in length × 60 mm in width × 1 mm in thickness. Then, the crosslinked rubber sheet was heated at 90°C for 3 hours in a nitrogen atmosphere, and then the temperature was raised to 305°C over 5 hours, maintained at 305°C, and further heated for 13 hours (secondary crosslinking).

[0222] The crosslinked rubber sheet after the secondary crosslinking was cooled to room temperature and then punched into a No. 4 dumbbell shape specified in JIS K 6251 to obtain three test pieces of the crosslinked rubber product 1 .

[0223] [Example 2~Example 7]

[0224] Fluorinated copolymers 2 to 7, fluorinated copolymer compositions 2 to 7, and test pieces of cross-linked rubber articles 2 to 7 of Examples 2 to 7 were obtained in the same manner as in Example 1, except that the types of monomers used, the addition ratio of initially added monomers, the addition ratio of later added monomers, the addition order of later added monomers, the number of repetitions of the addition order of later added monomers, the additional amount of polymerization initiator, and the polymerization conditions were changed to those shown in Tables 1-1 and 1-2.

[0225] [Example 8]

[0226] <Production of Fluorinated Copolymer 8>

[0227] After degassing a stainless steel pressure-resistant reactor with an internal volume of 20 L equipped with anchor blades, 7.2 L of ultrapure water, 880 g of a 30% by mass solution of C2F5OCF2CF2OCF2COONH4 as an emulsifier, 17.5 g of C3DVE, and 15.9 g of a 5% by mass aqueous solution of disodium hydrogen phosphate dodecahydrate were added to replace the gas phase with nitrogen. While stirring at a speed of 375 rpm using an anchor blade, 140 g of TFE and 631 g of PMVE were pressed into the container, and the internal temperature was raised to 80°C. The internal pressure of the reactor was 0.90 MPa [gauge]. 40 mL of a 3% by mass aqueous solution of ammonium persulfate (APS) was added to start polymerization. If the addition ratio of the monomers pressed before the start of polymerization (hereinafter also referred to as "initial added monomers") is expressed by molar ratio, it is TFE:PMVE:C3DVE=26.7:72.4:1.0.

[0228] As the polymerization proceeds, TFE is introduced when the pressure inside the reactor drops to 0.89 MPa [gauge], raising the pressure inside the reactor to 0.90 MPa [gauge]. This operation is repeated, and 90 g of PMVE is also introduced every time 110 g of TFE is introduced. In addition, when 30 g of TFE is introduced, 7.0 g of 1,4-diiodoperfluorobutane is introduced into the reactor together with 50 mL of ultrapure water using an ampoule tube. When the polymerization rate decreases, a 3% by mass aqueous solution of APS is appropriately added. The total amount of 3% by mass aqueous solution of APS added after the start of polymerization is 45 mL.

[0229] At the end of the cycle when the total added mass of TFE reached 990 g, 110 g of TFE was pressed in. When the total added mass of the post-added TFE reached 1100 g, the addition of the post-added monomers was stopped, and the temperature inside the reactor was cooled to 10° C. to stop the polymerization reaction and obtain a latex containing fluorinated copolymer 8. The polymerization time was 396 minutes. In addition, the total added mass of each post-added monomer was 1100 g for TFE and 810 g for PMVE, which was converted into a molar ratio of TFE:PMVE=69.3:30.7.

[0230] According to Example 1, the molar ratio of each unit in the fluorinated copolymer 8 obtained by aggregating the polymerized latex in a 5% by mass aqueous solution of potassium aluminum sulfate was: TFE unit: PMVE unit: C3DVE unit = 68.5: 31.2: 0.3. In addition, the content of iodine atoms in the fluorinated copolymer 8 calculated by a device combining an automatic sample combustion device, an ion chromatography pretreatment device (manufactured by Mitsubishi Chemical Analytech Co., Ltd., AQF-100 model) and an ion chromatograph was 0.20% by mass.

[0231] It should be noted that the filtrate after the latex after polymerization was aggregated and the fluorinated copolymer was taken out and the filtrate remaining after the latex was washed were filtered with a disk filter, and the obtained liquid was analyzed with an ion chromatograph. As a result, no fluoride ions were detected in an amount of 3% by mass or more relative to the input amount of C3DVE. Therefore, it was considered that all the C3DVE used in the feed was polymerized, and the content of C3DVE units relative to all units in the polymer was calculated based on the input amount of C3DVE.

[0232] <Production of Fluorinated Copolymer Composition 8>

[0233] The components were mixed in a ratio of 100 parts by mass of the fluorinated copolymer 8, 15 parts by mass of carbon black (Thermax N990 manufactured by Cancarb Co., Ltd.), 3 parts by mass of triallyl isocyanurate (TAIC WH-60 manufactured by Mitsubishi Chemical Corporation), 1 part by mass of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (PERHEXA 25B manufactured by NOF Corporation), and 1 part by mass of calcium stearate (manufactured by Kanto Chemical Co., Ltd.), and kneaded on a two-roll mill to obtain a fluorinated copolymer composition 8.

[0234] <Manufacturing of Cross-linked Rubber Article 8>

[0235] The fluorinated copolymer composition 8 was subjected to hot pressing (primary crosslinking) at 150° C. for 20 minutes, and then subjected to secondary crosslinking in an oven at 250° C. for 4 hours to obtain a crosslinked rubber sheet having a thickness of 1 mm. The crosslinked rubber sheet obtained after the secondary crosslinking was cooled to room temperature and then punched into a No. 4 dumbbell shape specified in JIS K 6251 to obtain three test pieces of the crosslinked rubber article 8.

[0236] The evaluation results of each example are shown in Table 1-1 and Table 1-2.

[0237] [Table 1-1]

[0238]

[0239] [Table 1-2]

[0240]

[0241] As shown in Table 1-1 and Table 1-2, it was confirmed that when using a TFE unit, a PAVE unit, a DVE unit and an R CN In addition, it was confirmed that the compression set of the cross-linked rubber product can be further reduced by using a fluorinated copolymer having a storage modulus G' of 470 kPa or more (Examples 1 to 6).

[0242] In contrast, it was confirmed that the use of a DVE unit or R CN In the case of using a fluorinated copolymer having no DVE unit or R CN When a cross-linked rubber obtained by a fluorinated copolymer containing 1,2-dimethyl-1-nitropropene units is heated to 300°C for a heat aging test, the test piece deforms, and thus the tensile strength, 100% modulus and tensile elongation cannot be measured.

[0243] It should be noted that the entire contents of the specification, claims, drawings, and abstract of Japanese Patent Application No. 2019-197115 filed on October 30, 2019 are cited herein and incorporated as a disclosure of the specification of the present invention.

Claims

1. A fluorinated copolymer comprising: a unit based on tetrafluoroethylene, a unit based on perfluoro(alkyl vinyl ether), a unit based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds, and a unit based on a monomer having a nitrile group and a fluorine atom, The molar ratio of the content of the unit based on the monomer having a fluorine atom and two or more polymerizable unsaturated bonds to the content of the unit based on the monomer having a nitrile group and a fluorine atom is 0.03 to 2, The monomer based on a fluorine atom and two or more polymerizable unsaturated bonds is CF2=CFO(CF2)3OCF=CF2 or CF2=CFO(CF2)4OCF=CF2. 2 . The fluorinated copolymer according to claim 1 , which has a storage modulus G′ of 470 kPa or more.

3. The fluorinated copolymer according to claim 1 or 2, wherein Perfluoro(alkyl vinyl ether) is a monomer represented by the following formula (1), CF2=CF-O-R f1 (1) In formula (1), R f1 It represents a perfluoroalkyl group having 1 to 10 carbon atoms.

4. The fluorinated copolymer according to any one of claims 1 to 3, wherein The monomer having a nitrile group and a fluorine atom is a monomer represented by the following formula (5), CR 51 R 52 =CR 53 -R 54 -CN (5) In formula (5), R 51 , R 52 and R 53 Each independently represents a hydrogen atom, a fluorine atom or a methyl group, and R 54 It represents a divalent perfluorocarbon group having 1 to 10 carbon atoms, or a group having an ethereal oxygen atom at the end of the perfluorocarbon group or between carbon-carbon bonds.

5. The fluorinated copolymer according to any one of claims 1 to 4, wherein The content of units based on tetrafluoroethylene is 59 to 80 mol %, the content of units based on perfluoro(alkyl vinyl ether) is 19 to 40 mol %, the content of units based on a monomer having a fluorine atom and two or more polymerizable unsaturated bonds is 0.01 to 1.0 mol %, and the content of units based on a monomer having a nitrile group and a fluorine atom is 0.05 to 5 mol %, relative to all units of the fluorinated copolymer.

6. The fluorinated copolymer according to any one of claims 1 to 5, wherein The fluorine-containing copolymer has iodine atoms. 7 . A fluorinated copolymer composition comprising the fluorinated copolymer according to claim 1 and at least one of a cross-linking agent and a catalyst. The fluorinated copolymer composition according to claim 7 , which does not substantially contain a release agent.

9. A cross-linked rubber article obtained by cross-linking the fluorinated copolymer in the fluorinated copolymer composition according to claim 7 or 8.